2020
DOI: 10.1007/s10734-019-00473-6
|View full text |Cite
|
Sign up to set email alerts
|

Sources of stress and scholarly identity: the case of international doctoral students of education in Finland

Abstract: Although stressors and coping strategies have been examined in managing stress associated with doctoral education, stress continues to have a permeating and pernicious effect on doctoral students' experience of their training and, by extension, their future participation in the academic community. International doctoral students have to not only effectively cope with tensions during their training and their socialization in their discipline but also address the values and expectations of higher education insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Finnish universities are responsible for the admission procedures, learning outcomes, supervision practices, and the assessment of doctoral programs and dissertations (Kivistö et al 2017). This high degree of autonomy in doctoral policies has greatly contributed to the increase in Finnish international doctoral recruitment (Pappa et al 2020). Correspondingly, the presence of international doctoral students has had a significant impact on many research fields in Finland, especially in the fields of science such as medicine, technology, mathematics, and engineering (Pyhältö et al 2012).…”
Section: The Context: Doctoral Education In Finlandmentioning
confidence: 99%
See 1 more Smart Citation
“…Finnish universities are responsible for the admission procedures, learning outcomes, supervision practices, and the assessment of doctoral programs and dissertations (Kivistö et al 2017). This high degree of autonomy in doctoral policies has greatly contributed to the increase in Finnish international doctoral recruitment (Pappa et al 2020). Correspondingly, the presence of international doctoral students has had a significant impact on many research fields in Finland, especially in the fields of science such as medicine, technology, mathematics, and engineering (Pyhältö et al 2012).…”
Section: The Context: Doctoral Education In Finlandmentioning
confidence: 99%
“…However, due to the different learning culture between Finland and China, they might be shocked by the unpredicted challenges and their inability to deal with academic difficulties effectively (Bai 2016;Mesidor and Sly 2016). Although the increasing amount of research referred to learning experiences of Chinese doctoral international students has been done based in universities in the United States, the United Kingdom, and Australia, our knowledge of Chinese doctoral students in Finnish universities is scarce (Aittola 2017;Pappa et al 2020). Therefore, given the significant proportion of Chinese students at Finnish campuses, and the limited research on Chinese doctoral students in Finland, this study aims to investigate learning experiences of Chinese doctoral students at Finnish universities.…”
Section: Introductionmentioning
confidence: 99%
“…Undertaking a doctoral degree provides both highs and lows, potentially significantly reducing or increasing PhD candidates’ well-being (e.g., Stubb et al, 2011 ; Divaris et al, 2012 ; Caesens et al, 2014 ; Hunter and Devine, 2016 ; Swords and Ellis, 2017 ). Yet, previous research on the topic has focused heavily on the negative attributes such as stress (e.g., Oswalt and Riddock, 2007 ; Pappa et al, 2020 ), depression (e.g. Peluso et al, 2011 ; Levecque et al, 2017 ), anxiety (e.g., Barry et al, 2018 ; Liu et al, 2019 ), and exhaustion (e.g., Hunter and Devine, 2016 ), while positive aspects of PhD experience have been studied to a lesser extent ( Barnes and Randall, 2012 ; Sverdlik et al, 2018 ; Pyhältö et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings were recently supported by a study conducted with eleven international doctoral students in six Finnish universities. These participants identified the principal sources of stress as intrapersonal regulation, challenges about doing research, and lack of a supportive network (Pappa et al, 2020). Orellana et al (2016) indicated that these challenges may add a burden to distance students who are still grappling with conducting autonomous research or working independently to develop new research-related skills that may lead to the successful completion of their studies.…”
Section: Literature Review the Importance Of Supplementing Distance Supervision With Face-to-face Tutorialsmentioning
confidence: 99%